2013
DOI: 10.1097/ppo.0b013e31829da0ae
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Tumor Microenvironment as a Novel Target of Renal Cell Carcinoma Therapeutics

Abstract: To move forward with immunotherapy it is important to understand how the tumor microenvironment generates systemic immunosuppression in patients with renal cell carcinoma (RCC) as well as in patients with other types of solid tumors. Even though antigen discovery in RCC has lagged behind melanoma, recent clinical trials have finally authenticated that RCC is susceptible to vaccine-based therapy. Furthermore, judicious coadministration of cytokines and chemotherapy can potentiate therapeutic responses to vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 113 publications
(171 reference statements)
0
28
0
1
Order By: Relevance
“…In metastatic RCC, sunitinib as monotherapy has shown high objective response rates (up to 50 %) and currently is the first-line treatment option for metastatic RCC patients [79]. In addition to normalizing the tumor vascularization, this drug promotes anti-tumor immunity through different mechanisms [80].…”
Section: Therapies That Modulate the Tumor Microenvironmentmentioning
confidence: 99%
“…In metastatic RCC, sunitinib as monotherapy has shown high objective response rates (up to 50 %) and currently is the first-line treatment option for metastatic RCC patients [79]. In addition to normalizing the tumor vascularization, this drug promotes anti-tumor immunity through different mechanisms [80].…”
Section: Therapies That Modulate the Tumor Microenvironmentmentioning
confidence: 99%
“…To evaluate the systemic percentages of these immunosuppressive cells in subjects with clear cell RCC vs. healthy controls, we analyzed 4 different MDSC phenotypes based on recent literature [13,2527]. We found that MDSC population 1 (HLA-DR neg CD14 + ) was significantly increased in subjects with clear cell RCC relative to healthy controls, in whom this cell population was negligible (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…MDSC suppress T-cell effector and natural killer cell function and also regulate macrophage cytokine production. Unlike murine MDSC definitions, which are characterized by distinct CD11b + Ly6C + (monocytic) or CD11b + Ly6G + (granulocytic) phenotypes, a number of different MDSC phenotypes have been reported in humans [13,2527]. However, recent literature indicates that MDSCs express CD14 or CD33 or both and lack HLA-DR [13,15,27,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renal cell carcinoma (RCC) is known to be resistant to conventional chemotherapeutic agents and is known to induce an immunosuppressive environment. Although tyrosine kinase inhibitors (TKIs), including sorafenib and sunitinib, are widely utilized for the treatment of patients with metastatic RCC and TKIs are expected to act as adjuvants for immunotherapeutic effects (3,4), the anticancer effects of TKIs may be unable to overcome the immunosuppressive microenvironment of RCC hosts (5).…”
Section: Introductionmentioning
confidence: 99%